Factors influencing the formation of creative student teams - Y. V. Ushakova; D. V. Zernov; I. V. Sitnikova (Russian State Vocational Pedagogical University, 2024)
Introduction. The research relevance is determined by the needs of Russian societal development in attracting active and talented youth to various spheres of economic and social activities. Aim. The present research aimed to identify the factors that contribute to the formation of creative student teams capable of effectively engaging in activities within the creative industry, research, scientific-technological projects, and socially significant projects. Methodology and research methods. The empirical basis of the article was the results of a sociological study on university students' creativity using a questionnaire survey method. Through factor analysis, five groups of students were identified with conventional names: optimists, populists, versatile, disciplined, and outsiders. Results. The analysis of the research results allowed the authors to define the main parameters and present a typology of students based on their attitudes towards different types of activities, involvement in scientific and social university life, evaluations of the conditions of scientific, educational, and social activities at the university, engagement in social networks, and identification of the most crucial components of life success. Scientific novelty. On the basis of the authors' methodology of sociological research on the creativity of university students, approaches to forming creative student teams are proposed. Practical significance. The practical significance of the article lies in the potential utilisation of the proposed methodology and the study results by teachers and specialists at universities involved in engaging students in research, creative endeavors, and socially significant projects.